Deformation and fracture of SiCp/Al composites under complex loading conditions: A simulation study - Chenjun Ye; Kang Wang; Qiubao Ouyang; Zan Li; Di Zhang (Journal of Materials Research and Technology, 2024)
An accurate depiction of the deformation and fracture mechanisms of metal matrix composites is the key to their rational structure and property design. In the present work, the Advanced Guerson Tvergaard Needleman (AGTN) constitutive model is firstly combined with an algorithm to reconstruct realistic 3D microstructures within the finite-element framework. We employ this model to probe the elastoplastic response and fracture behaviors of aluminum matrix composites with different volume fractions of reinforcing particles (7, 14, and 21 %) and under various loading conditions (tension, compression and shear). Real microstructures are referred to reconstruct the three-dimensional model of the composites. The AGTN constitutive model is integrated with the micromechanical damage model, which is capable of independently describing the constitutive behavior of various components, including the elastoplastic damage of the metal matrix, particle-enhanced elastic-brittle failure, and the interfacial traction separation. By using the conventional SiCp/Al composite system as a model material, we examine the stress state of the matrix and fracture mechanisms under different loading conditions by using triaxiality, Lode angle and statistical analysis. In general, the damage of SiCp/Al composites can be attributed to interfacial debonding and particle fracture, whereas the latter dominates when the volume fraction of SiCp is high. Furthermore, the critical volume fraction for the transition of damage mechanisms is found to be largely dependent on the loading conditions. Our work provides a comprehensive understanding of particle-reinforced aluminum matrix composite under in-service conditions.